Strabismic Adults' Expectations of Psychosocial Support From Healthcare Professionals–A Qualitative Descriptive Study - Anna Mason; Katja Joronen; Laura Lindberg; Marika Kajander; Nina Fagerholm; Anja Rantanen (Health Science Reports)
ABSTRACT Background and Aims Strabismus, an eye misalignment, impacts the functional and psychosocial health‐related quality of life in adult patients. Corrective surgery generally improves adults' health‐related quality of life. Previous research reports that strabismic adults with a psychosocial influence of the condition may benefit from preoperative psychosocial support, although what such support should consist of is unclear. Therefore, this study aimed to describe strabismic adults' expectations of psychosocial support from healthcare professionals. Methods The study has a qualitative descriptive design. It included 12 semi‐structured interviews with purposefully recruited patients who had experienced the psychosocial influences of strabismus. The data were analyzed by inductive content analysis. Results Strabismic adult patients described their expectations for psychosocial support, consisting of education about strabismus, genuine encounters with strabismus experts, accessible support, and available peer support. The participants explained that strabismus specialists should provide tailored education for patients, the public, and other healthcare professionals. They shared that strabismus professionals should ask about patients' psychosocial well‐being—that by intently listening, openly discussing, and validating patients' experiences, they could support their well‐being. Psychological care provided by nurses and psychologists should be easily accessible, supportive, and timely for children and adolescents. Participants also expected professionals to guide them to available peer support. Conclusion Strabismic adult patients dealing with the condition's psychosocial burden expect psychosocial support from strabismus experts. This study's results can be used to improve psychosocial care in clinical strabismus services.